(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
The digital economy has emerged as a powerful force in driving economic growth and development globally. Uzbekistan, as a country with immense potential, ispoised to leverage IT platforms, new technologies, and innovative business models in order to propel its modernization and economic development. This article explores various ways in which Uzbekistan can harness the power of digital technologies to drive its digital economy forward.